2018
DOI: 10.1530/rep-17-0485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of activins A and B in the adult mouse epididymis and vas deferens

Abstract: Activin A regulates testicular and epididymal development, but the role of activin B in the epididymis and vas deferens is unknown. Mouse models with reduced activin A ( and ), or its complete absence (), were investigated to identify specific roles of activins in the male reproductive tract. In 8-week-old mice, serum activin A decreased by 70%, with a 50% reduction of gene expression and protein in the testis, epididymis and vas deferens. Activin B and the activin-binding protein, follistatin, were similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Since Inhba −/− mice die at birth (Matzuk et al ., 1995a), we used heterozygous Inhba +/− mice, which show a 50% reduction in serum and tissue activin levels, to study the effects of activin A in the adult. It was shown that 50% of normal activin levels were sufficient to maintain epididymal structure and function in the adult, as the Inhba +/− mice were comparable to their wild‐type littermates in their epididymal morphology, overall epididymal gene expression and fertility (Wijayarathna et al ., 2018b).…”
Section: Activin‐deficient Mouse Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Inhba −/− mice die at birth (Matzuk et al ., 1995a), we used heterozygous Inhba +/− mice, which show a 50% reduction in serum and tissue activin levels, to study the effects of activin A in the adult. It was shown that 50% of normal activin levels were sufficient to maintain epididymal structure and function in the adult, as the Inhba +/− mice were comparable to their wild‐type littermates in their epididymal morphology, overall epididymal gene expression and fertility (Wijayarathna et al ., 2018b).…”
Section: Activin‐deficient Mouse Modelsmentioning
confidence: 99%
“…It is significant, moreover, that the regional pattern of Ido1 expression follows that of the activins, which are constitutively biologically active, and not that of the TGF‐β subtypes, which are produced as latent precursors. It was noted that Ido1 did not decrease in response to reduced activin levels in the Inhba +/− mice, indicating that 50% of normal activin A, possibly in combination with activin B, is sufficiently robust to maintain Ido1 expression in the caput epididymis (Wijayarathna et al ., 2018b).…”
Section: The Relationship Between Activin and Immunoregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…As activins and TGF-βs both signal through SMAD2/3, one cannot rule out a contribution of activin signalling to the signal detected by Western blot analyses. However, this contribution is not expected to question the importance of the corpus region as ACTIVIN A was shown to be homogeneously present throughout the murine epididymis while ACTIVIN B was more present in the caput than in the cauda region 23,28 . On the contrary, TGF-β signalling may be underestimated in this study because TGF-β signalling pathways independent of SMAD, involving PI3K and various MAP kinases, have been described 29 .…”
Section: Discussionmentioning
confidence: 99%